Genetic Diversity and Population Genetic Structure of Setosphaeria turcica From Sorghum in Three Provinces of China Using Single Nucleotide Polymorphism Markers - Cui, Linkai; Deng, Junli; Zhao, Linxi; Hu, Yanhong; Liu, Tingli (Frontiers in Microbiology, 2022)
Setosphaeria turcica is a heterothallic fungus that is the causal agent of northern leaf blight (NLB), which is a devastating foliar disease of sorghum and maize. Despite of its adversary to crop production, little is known about the genetic diversity and population genetic structure of this pathogen from sorghum. In this study, we explored the utilization of single nucleotide polymorphism (SNP) molecular markers and three mating type-specific primers to analyze the genetic diversity, population genetic structure and mating type distribution of 87 S. turcica isolates that had been collected in sorghum production areas from three provinces, including Henan, Shaanxi and Shanxi in China. The populations are featured with moderate genetic diversity and relatively equal mating type distribution of MAT1-1 and MAT1-2. The genetic differentiation was significant (P < 0.05) among different populations except those from Henan and Shanxi provinces that showed particularly frequent gene flow between them. Neither the neighbor-joining phylogenetic tree, nor principal coordinate analysis, nor genetic structure analysis was able to completely separate the three populations. The relatively low genetic distance and high genetic identification were also observed among the three populations. Nevertheless, the genetic variation within populations was the major source of variation as revealed by AMOVA analysis. The findings of this study have improved our current understanding about the genetic diversity, population genetic structure, and the distribution of mating type of S. turcica, which are useful for unraveling the epidemiology of NLB and developing effective disease management strategies.